A longitudinal study of serum insulin‐like growth factor‐I levels over 6 years in a large cohort of children and adolescents with type 1 diabetes mellitus: A marker reflecting diabetic retinopathy. Issue 5 (2nd May 2018) - Öberg, Daniel; Salemyr, Jenny; Örtqvist, Eva; Juul, Anders; Bang, Peter
Abstract : Objective: To evaluate longitudinal serum insulin‐like growth factor‐I (IGF‐I) in a large cohort of children and adolescents with type 1 diabetes in relation to hemoglobin A1c (HbA1c), age, diabetes duration, and body mass index (BMI), its association to height and retinopathy, and in comparison with healthy subject references. Methods: A total of 2683 serum IGF‐I values were obtained from 806 children and adolescents with T1DM, from annual blood samples for up to 6 consecutive years. Results: In a multiple regression analysis IGF‐I values were negatively correlated to HbA1c and diabetes duration, and positively correlated to BMI ( P  < .001, P  < .001, and P  < .001, respectively, adjusted r 2  = 0.102). Children and adolescents with T1DM had lower mean IGF‐I levels and reference interval limits compared to healthy subjects. In boys, mean (SD) IGF‐I SD score (SDS) levels were −1.04 (±1.3) calculated from the healthy reference. IGF‐I peaked at 15 years of age, similarly to healthy controls, but with markedly lower levels in late puberty. Girls were more affected at later stages of puberty but with a slightly less depressed overall mean IGF‐I SDS of −0.69 (±1.2). In a subgroup of 746 subjects with fundus photography, a negative correlation was seen between individual mean IGF‐I SDS and preproliferative retinopathy ( P  = .004, adjusted r 2  = 0.021). In another subgroup of 84 adolescents, no correlation was seen between individual mean IGF‐I SDS and target height SDS or distance to target height SDS. Conclusion: Poor metabolic control and diabetes duration impact negatively on serum IGF‐I levels. A low individual mean IGF‐I level was associated with progression of retinopathy independently of HbA1c, age, gender, and diabetes duration. Disease, sex and age related IGF‐I SDS may become clinical helpful as a supplement to HbA1c in predicting the long‐term outcome for children and adolescents with T1DM.